EFEKTIVITAS METODE GERAK DAN LAGU UNTUK MENINGKATKAN KECERDASAN KINESTETIK PADA ANAK USIA DINI - Depi Nursiti; Lukman Hamid; Nisa Nurhidayah (Sekolah Tinggi Agama Islam (STAI) Al Hidayah Tasikmalaya, 2020)
Early childhood is in the golden age stage. This stage is marked by significant changesin aspectsof its development (such as : language, art and physical motor). So that at this stage can be passed well by every child it is necessary to strive for proper education. Including the development of musical intelligence and kinesthetic intelligence, children must also develop. One of the lessons that can be done by the teacher is learning motion and songcan influence and control the nerve center, and help children to further develop their intelligence not only in aspects of cognitive, language and emotional development but aslo in the development of art and physical children. This study aims to determine the effectiveness of kinesthetic intelligence in early childhood whit the motion and song method in RA Ar-Arahmah Kawalu. The research method used is a qualitative approach whita descriptive method for class B RA Ar-Rahmah Kawalu Tasikmalaya.